Modern trends of public policy’s subjectivity change - E. M. Chaltseva (Granì, 2016)
The problem of an institutionalization of public actors and forms of their interaction in contemporary post-modern political space has been analyzed in the article. New tendencies of their subjectivity’s change concerning the formation of the public equity in various types of the modes have been considered: hybridization, individualization, cross-border, conflict and the transformation of the network entities. Information technologies has become to be one of the main instruments of implementation of public policy in modern political conditions, which, in the long term, can be considered as a basis for a transformation of political systems of all types. Change of roles of political subjects is connected with such sociocultural characteristic of the present stage of society’s development as individualization. The individualized subject is in a constant process of formation of their own identity and they look for valuable grounds and orientations in behavioral practice using mechanisms of identification and socialization. Consequently, the social positioning of the individual, identification of individual with the interests and values happens. Change in nature of identity and political culture shows the importance of the following tendency in political practice as a hybridism. Today there are a lot of examples of a hybridism: hybrid modes, states, batches, etc. Interactions between actors of public policy get more and more nonhierarchical nature and the value of horizontal negotiation network model increases. Various forms of transitional states created the same variety of national public ones. For the public policy in transformed states the most actual are such problems as: imitating nature, institutional uncertainty, conflict, institutional “traps”. The key mechanism of the political practice of development of actors is the conversion of different types of resources into the public equity, which is a part of the political equity. The public actors that act in specific institutional regime frameworks possess the incorporated capability to participate in collective and individual actions. This participation is based on their interests, preferences and identity. It has been shown in the article that public actors, which act in a certain environment regime, create special forms of the public equity which reflect efficiency rate, openness and level of conflict of the political system.